Caracterización físico-química y mineralógica del material de la Concesión Minera “Nicolas 1” Código Catastral (102826), para el mejoramiento del proceso de beneficio, en la parroquia El Carmen de Pijilí, cantón Camilo Ponce Enríquez, Provincia del Azuay. - Rojas Guano, Sergio Estuardo (2023)
It is widely known that mining, whether small or large, is a preferred investment for businessmen across the globe due to its high income, both for the investor and the government. Ecuador is a country with mining potential. It has gold, silver and copper reserves. According to the Central Bank of Ecuador, minerals are the third most exported non-oil product. The present research work is focused on the physical, chemical and mineralogical characterization of the Nicolas 1 mining concession material for the improvement of the beneficiation process. There is a cadastral code 102826 for this parcel, located in the Ponce Enriquez canton, El Carmen de Pijili parish. For this study, physical, chemical and mineralogical characterization tests were carried out to identify the chemical composition and structure of the minerals, also the head analysis of the main minerals such as gold, silver, copper and arsenic was carried out to know in what quantity each of them is present in order to evaluate if the vein to be exploited is economically profitable. The petrographic analysis in the study zone determined the presence of pyrite, arsenopyrite, feldspars and carbonates. Moreover, gold is encapsulated in arsenopyrite, so arsenic values are representative. The sample VSMBO-SR002 contained a value of 11.54 % of arsenic and the lowest value was 0.10% in the sample VPBBO-SR003. To recover gold, metallurgical methods such as cyanidation and flotation were applied. It was confirmed that gold is encapsulated in arsenopyrite. Both methods recovered 1.65 g/t. This concluded that the most suitable method for gold recovery was cyanidation despite its arsenic content. Keywords: Physical-chemical analysis, mineralogical analysis, mineral beneficiation processes. Metallurgy,